2021
DOI: 10.1002/leg3.101
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical basis of resistance to pod borer (Helicoverpa armigera) in Australian wild relatives of pigeonpea

Abstract: The domestication of pigeonpea has severely impacted the intrinsic host‐plant resistance (HPR) to pest and diseases, particularly pod borer (Helicoverpa armigera hubner). This study with 41 Australian wild Cajanus genotypes and interspecific hybrids demonstrated a high level of resistance to H. armigera in the accessions of Cajanus acutifolius, C. latisepalus, C. lanceolatus, C. pubescens, and C. reticulatus var. reticulatus. Significant variation in herbivory development and mortality (P < 0.001) was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…In our neonate performance experiment, larvae were allowed to select their own feeding site, as opposed the constraints typically placed on them in standard ‘Petri dish assays’ where larvae are confined to feeding on a particular plant part. 36 , 37 , 38 , 39 , 40 Previous studies have shown that first instar H. armigera larvae have a behavioural tendency to move upwards on plants and locate flowers as feeding sites. 41 , 55 , 56 , 57 In our study, after 72 h, regardless of their initial placement location, almost all larvae were found feeding inside flowers, sites devoid of trichomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our neonate performance experiment, larvae were allowed to select their own feeding site, as opposed the constraints typically placed on them in standard ‘Petri dish assays’ where larvae are confined to feeding on a particular plant part. 36 , 37 , 38 , 39 , 40 Previous studies have shown that first instar H. armigera larvae have a behavioural tendency to move upwards on plants and locate flowers as feeding sites. 41 , 55 , 56 , 57 In our study, after 72 h, regardless of their initial placement location, almost all larvae were found feeding inside flowers, sites devoid of trichomes.…”
Section: Discussionmentioning
confidence: 99%
“…28,31,32,34,36 Despite the limitations of such approaches, even recent studies persist in screening pigeonpea genotypes with detached-leaf assays. [37][38][39][40] The conditions created in these experiments ignore the behavioural 'choice' of H. armigera larvae, in particular intra-plant movement as larvae tend to move up plants and select floral structures or terminal leaves as feeding sites, [41][42][43] along with detecting and avoiding induced plant defences. 6,44 In this study we evaluated three cultivars of short-duration pigeonpea for resistance against H. armigera (ICPL 87, ICPL 86012, and ICPL 88039) (Table 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondary metabolites involved in plant–herbivore interactions are products of the phenylpropanoid pathway and comprise flavonoids viz., flavanones, flavonols, flavanols, and anthocyanins. Flavonoids are a group of multiuse low molecular weight secondary metabolites that have proven to play vital roles in various plant physiological activities and defence against biotic and abiotic stresses [ 11 , 16 , 17 ]. During the assessment of pod borer resistance response in C. platycarpus, it was observed that there was a structured reprogramming of flavonoid biosynthesis pathway leading to the hyper-accumulation of several flavonoids [ 11 ].…”
Section: Introductionmentioning
confidence: 99%